Preparation method of self-supporting electrolytic water anode of bimetallic site oxygen coupling electrolytic acidic medium oxygen evolution catalyst

By using a bimetal site oxygen-coupled electrolytic acidic dielectric oxygen evolution catalyst in an acidic environment, the problem of low OER performance in an acidic environment is solved, and a catalytic effect is achieved with high efficiency, stability and low cost.

CN119593005APending Publication Date: 2025-03-11ZHONGBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411869572.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art has the kinetic hysteresis of the anode oxygen evolution reaction (OER) during water electrolysis under acidic environments, high energy consumption and low catalyst efficiency. Especially in acidic media, the activity and stability of the catalyst are limited, making it difficult to adapt to industrial applications.

Method used

The preparation method of a self-supported electrolytic water anode of bimetal site oxygen-coupled electrolytic acidic medium oxygen evolution catalyst is used to prepare catalytic electrodes by mixing nitrate oscillation ball milling, without adding precious metals.

Benefits of technology

It significantly improves the OER performance in an acidic environment, enhances the corrosion resistance and catalytic activity of the catalyst, extends the service life of the catalyst, reduces energy loss, reduces dependence on precious metals, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593005A_ABST
    Figure CN119593005A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a self-supporting electrolytic water anode of a bimetallic site oxygen coupling electrolytic acidic medium oxygen evolution catalyst, and belongs to the technical field of electro-catalysis electrode preparation and electrochemistry. The method comprises the following steps: firstly preparing a 2.0 M nitrate aqueous solution, mixing according to a non-noble metal equimolar ratio, taking the mixed solution, adding the mixed solution into a PE (Poly Ethylene) ball milling tank for ball milling, mixing the ball-milled solution with ethanol for ultrasonic treatment to obtain a catalytic solution, smearing the catalytic solution on a carrier, drying under an infrared lamp, and finally annealing in a muffle furnace. According to the method, precious metal is not needed, the prepared catalyst self-supporting electrolytic water anode is excellent in OER performance, durability, energy conversion efficiency and the like in the acid environment, the preparation process is simple, raw materials are easy to obtain, the product is stable, and the industrial application potential is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrocatalytic electrode preparation and electrochemical technology, and particularly relates to the preparation of a bimetallic catalytic electrode, specifically a method for preparing a self-supporting water electrolysis anode of a bimetallic site oxygen-coupled electrolytic acidic medium oxygen evolution catalyst. Background Art

[0002] In the exploration and development of clean energy technology, water electrolysis is an important way to obtain hydrogen energy and is receiving widespread attention worldwide. However, the anodic oxygen evolution reaction (OER) in the water decomposition process, as a key technical link in the water electrolysis process, faces kinetic hysteresis, high energy consumption and low catalyst efficiency. Due to its high energy barrier, it has become a key bottleneck restricting the efficiency of the entire system, especially under acidic working conditions.

[0003] Although the common OER catalysts on the market currently perform well in alkaline electrolytes, their activity and stability in acidic systems are greatly limited, making it difficult to adapt to a wider range of industrial application scenarios. Although OER research has made significant progress in recent years, especially in the development of catalysts for alkaline electrolyzers, there are still many technical bottlenecks in OER under acidic media. OER under acidic conditions requires more powerful catalysts to resist corrosion and improve activity, but existing technologies often cannot meet these harsh conditions. Most current catalysts rely on precious metals such as platinum, iridium, and ruthenium. Although they perform extremely well in alkaline media, their extremely high cost, scarce resources, and loss of activity in acidic environments seriously hinder their widespread application. In recent years, the search for efficient and low-cost oxygen evolution catalysts has become a research hotspot.

[0004] In the field of electrocatalysis, single-atom catalysts are currently widely used, mainly relying on single atoms of precious metals, which are dispersed at the atomic level, effectively suppressing the reduction in activity caused by the aggregation of nanoparticles, thereby showing catalyst performance superior to that of traditional nanoparticles in OER. However, even in alkaline media, the cost of single-atom catalysts and resource constraints of rare metals are still issues that cannot be ignored, not to mention that under acidic conditions, due to the influence of the highly corrosive environment, the stability of these catalysts often decreases significantly, limiting their scope of application.

[0005] In response to the above challenges, the emerging concept of bimetallic site oxygen-coupled catalysts has emerged. This type of catalyst cleverly combines the properties of two or more metals, and creates new active centers by finely regulating the electron transfer and synergy between metals. Compared with single metal sites, bimetallic sites can form unique electronic structures, adjust the adsorption free energy of reaction intermediates, and thus optimize catalytic performance. Of particular importance is that such a design allows the catalyst to exhibit better corrosion resistance and higher OER activity in acidic media, providing a broader range of applicable scenarios for hydrogen production by water electrolysis. It not only reduces the dependence on rare metals, but also solves the stability problem of single-atom catalysts in acidic environments to a certain extent. The development of this type of catalyst marks a major step towards more efficient, economical and sustainable OER technology. Summary of the invention

[0006] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art, and to provide a method for preparing a self-supporting electrolytic water anode of a bimetallic site oxygen-coupled electrolytic acidic medium oxygen evolution catalyst. The method is a method for preparing a catalytic electrode by nitrate mixed vibration ball milling thermal decomposition, and the method can obtain a working electrode with excellent performance and stability without adding precious metals.

[0007] The present invention is achieved through the following technical solutions: A method for preparing a self-supporting anode for water electrolysis using a bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst comprises the following steps: 1) Dissolve two nitrates separately in deionized water to prepare two 2.0 M nitrate aqueous solutions.

[0008] 2) The two nitrate aqueous solutions prepared in step 1) are mixed in an equimolar ratio of the non-precious metals to obtain a mixed solution.

[0009] 3) Select the mixed solution prepared in step 2) and add it into a PE ball mill and shake it thoroughly.

[0010] 4) The mixed solution after sufficient oscillation in step 3) is mixed with ethanol and subjected to ultrasonic treatment to improve the wettability of the mixed solution to obtain a catalytic solution.

[0011] 5) Apply the catalytic solution prepared in step 4) on the carrier, apply the catalytic solution on both the front and back sides of the carrier, and dry under an infrared lamp.

[0012] 6) placing the carrier loaded and dried in step 5) in a muffle furnace, heating it to 400° C. and annealing it in air, and finally obtaining the bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst self-supporting water electrolysis anode.

[0013] Furthermore, in step 1), the two 2.0 M nitrate aqueous solutions prepared are any two of Co(NO3)2·6H2O, Ni(NO3)2·6H2O, and Fe(NO3)3·9H2O.

[0014] Furthermore, in step 1), the two 2.0 M nitrate aqueous solutions prepared are Co(NO3)2·6H2O and Ni(NO3)2·6H2O.

[0015] Furthermore, in step 3), 2 ml of the mixed solution was added to a PE ball mill, and then zirconium oxide microspheres were added. The speed was set to 5000 rpm and the time was 180 s. The mixture was fully shaken 10 times every half an hour.

[0016] Furthermore, in step 4), the mixed solution after sufficient shaking is mixed with ethanol in an equal volume ratio of 1:1, and the ultrasonic treatment time is 30 minutes.

[0017] Furthermore, in step 5), the carrier is raw carbon paper TGPH060.

[0018] Furthermore, the cutting size of the raw carbon paper TGPH060 is 1*2 cm, the amount of the catalytic solution applied on the front and back sides is 40 μl, the application area is 1*1 cm, and the drying time under the infrared lamp is 10 min.

[0019] Furthermore, in step 6), after the carrier is placed in the muffle furnace, the temperature of the muffle furnace is increased to 400° C. at a rate of 5° C. / min, maintained for 1 hour, and then cooled naturally.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1) The present invention significantly improves the OER performance in an acidic environment. In the field of traditional OER catalysts, especially in acidic media, the stability and activity of materials have always been technical difficulties. The present invention greatly enhances the antioxidant properties and catalytic activity of the catalyst under acidic conditions by precisely designing the synergistic effect between the bimetallic sites, effectively making up for the shortcomings of previous technologies.

[0021] 2) The present invention enhances the durability and reliability of the catalyst. Conventional catalysts are prone to performance degradation due to corrosion or degradation during long-term operation. The bimetallic structure in the present invention optimizes the matching of metal components and the heat treatment process to build a more solid crystal framework, extend the service life of the catalyst, and reduce the additional cost caused by frequent replacement.

[0022] 3) The present invention improves energy conversion efficiency. Due to the special properties of the OER reaction in acidic media, conventional catalysts often require a higher overpotential to start. The catalyst of the present invention significantly reduces the required overpotential through the ingenious layout of the bimetallic sites, greatly reducing the energy loss in the water electrolysis process, thereby improving the overall energy conversion efficiency.

[0023] 4) The present invention uses non-precious metals as catalyst components, avoiding excessive reliance on scarce and price-volatile precious metals, thereby reducing production costs. At the same time, by optimizing the preparation process, such as ball milling technology and ethanol-assisted uniform coating, it further saves raw materials and energy consumption, and improves economic benefits.

[0024] 5) The preparation process of the present invention is simple, the raw materials are easily available, the product is stable and reliable, and it has good potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic diagram of the catalytic solution obtained by mixing equal volumes of Co(NO3)2·6H2O, Ni(NO3)2·6H2O, and Fe(NO3)3·9H2O with ethanol in the present invention.

[0026] Figure 2 This is a schematic diagram of the self-supported water electrolysis anode of the Co(NO3)2·6H2O and Ni(NO3)2·6H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst prepared in Example 1 of the present invention.

[0027] Figure 3 This is a graph showing the test results of the electrolysis stability of the self-supported water electrolysis anode of the Co(NO3)2·6H2O and Ni(NO3)2·6H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst prepared in Example 1 of the present invention in 0.5M H2SO4 solution.

[0028] Figure 4 The Co(NO3)2·6H2O and Ni(NO3)2·6H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst self-supporting electrolytic water anode prepared in Example 1 of the present invention is 10mA / cm 2 Schematic diagram of operation under current density.

[0029] Figure 5 This is a graph showing the test results of the electrolysis stability of the self-supported water electrolysis anode of the Co(NO3)2·6H2O and Fe(NO3)3·9H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst prepared in Example 1 of the present invention in 0.5M H2SO4 solution. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments.

[0031] The traditional oxygen evolution reaction (OER) faces many problems in acidic media, such as kinetic hysteresis, high energy consumption, and low catalyst efficiency. In addition, the common OER catalysts have limited activity and stability in acidic systems, and the catalysts that rely on precious metals are costly and scarce in resources. The present invention provides a method for preparing a working electrode with excellent performance and stability without adding precious metals. The method first prepares a 2.0M nitrate aqueous solution and mixes it in an equimolar ratio of non-precious metals, takes the mixed solution and adds it to a PE ball milling jar for ball milling, mixes the ball-milled solution with ethanol by ultrasound to obtain a catalytic solution, applies the catalytic solution to raw carbon paper and dries it under an infrared lamp, and finally anneals it in a muffle furnace. The method of the present invention does not require precious metals, and the prepared catalyst self-supporting electrolytic water anode has excellent OER performance, durability, energy conversion efficiency, etc. in an acidic environment. The preparation process is simple, the raw materials are easily available, the product is stable, and it has the potential for industrial application.

[0032] In order to more clearly illustrate the preparation method and performance of the self-supporting water electrolysis anode of the bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst of the present invention, it is further illustrated by specific examples below. It should be particularly noted that the specific examples described herein are only used to explain the present invention and are not intended to limit the present invention. Example 1

[0033] A method for preparing a self-supporting anode for water electrolysis using a bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst comprises the following steps: 1) Prepare 2.0 M Co(NO3)2·6H2O aqueous solution and 2.0 M Ni(NO3)2·6H2O aqueous solution with deionized water.

[0034] 2) The Co(NO3)2·6H2O aqueous solution and the Ni(NO3)2·6H2O aqueous solution prepared in step 1) are thoroughly shaken and mixed in an equimolar ratio of Co and Ni to obtain a mixed solution of Co(NO3)2·6H2O and Ni(NO3)2·6H2O.

[0035] 3) Select 2 ml of the mixed solution of Co(NO3)2·6H2O and Ni(NO3)2·6H2O prepared in step 2) and add it to a PE ball mill, then add zirconium oxide microspheres, set the parameters of speed to 5000 rpm and time to 180 s, and oscillate 10 times every half an hour to ensure sufficient mixing and uniform oscillation; wherein, the PE ball mill is a micro high-speed vibration ball mill, model MSK-SFM-12M-220V.

[0036] 4) The mixed solution of Co(NO3)2·6H2O and Ni(NO3)2·6H2O after sufficient shaking in step 3) was mixed with ethanol in an equal volume ratio of 1:1 and subjected to ultrasonic treatment for 30 minutes to improve the wettability of the mixed solution to obtain a catalytic solution, such as Figure 1 As shown in b.

[0037] 5) Use a paper cutter to cut 1*2cm raw carbon paper TGPH060 as a carrier.

[0038] 6) Apply the catalytic solution prepared in step 4) on the raw carbon paper TGPH060 cut to a size of 1*2 cm. The catalytic solution is applied to both sides of the raw carbon paper TGPH060. The amount of catalytic solution applied on each side is 40 μl and the application area is 1*1 cm. Apply continuously to ensure that the applied catalytic solution is evenly distributed. Finally, dry under an infrared lamp for 10 minutes.

[0039] 7) The raw carbon paper TGPH060 loaded and dried in step 6) is placed in a muffle furnace, and the temperature of the muffle furnace is raised to 400°C at a rate of 5°C / min. After maintaining for 1 hour, the temperature is naturally cooled to obtain a self-supporting electrolytic water anode of a Co(NO3)2·6H2O and Ni(NO3)2·6H2O bimetallic site oxygen-coupled electrolytic acidic medium oxygen evolution catalyst. The actual object is shown in FIG. Figure 2 shown.

[0040] The electrochemical performance of the Co(NO3)2·6H2O and Ni(NO3)2·6H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst self-supporting water electrolysis anode prepared by the method of this embodiment is tested as follows: In 25 o C, in 0.5M H2SO4 solution, a three-electrode system was used with a graphite rod as the counter electrode, Hg / Hg2SO4 as the reference electrode, and the Co(NO3)2·6H2O and Ni(NO3)2·6H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst self-supporting water electrolysis anode prepared by the method of this embodiment as the working electrode, and the catalytic performance of the working electrode was tested using a CHI660e electrochemical workstation.

[0041] Figure 3 This is a graph showing the test results of the electrolysis stability of the Co(NO3)2·6H2O and Ni(NO3)2·6H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst self-supported electrolytic water anode prepared in this embodiment in 0.5M H2SO4 solution. From the analysis of the graph, it can be seen that the change in oxygen evolution potential is extremely small, which proves the extremely strong stability of the Co(NO3)2·6H2O and Ni(NO3)2·6H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst self-supported electrolytic water anode.

[0042] Figure 4 The Co(NO3)2·6H2O and Ni(NO3)2·6H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst self-supported electrolytic water anode prepared in this example is 10mA / cm 2 Schematic diagram of operation under current density of . It can be seen from the figure that its operation is very stable. Example 2

[0043] A method for preparing a self-supporting anode for water electrolysis using a bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst comprises the following steps: 1) Prepare 2.0 M Co(NO3)2·6H2O aqueous solution and 2.0 M Fe(NO3)3·9H2O aqueous solution with deionized water.

[0044] 2) The Co(NO3)2·6H2O aqueous solution and the Fe(NO3)3·9H2O aqueous solution prepared in step 1) are thoroughly shaken and mixed in an equimolar ratio of Co and Fe to obtain a mixed solution of Co(NO3)2·6H2O and Fe(NO3)3·9H2O.

[0045] 3) Select 2 ml of the mixed solution of Co(NO3)2·6H2O and Fe(NO3)3·9H2O prepared in step 2) and add it to a PE ball mill, then add zirconium oxide microspheres, set the parameters of speed to 5000 rpm and time to 180 s, and oscillate 10 times every half an hour to ensure sufficient mixing and uniform oscillation; wherein, the PE ball mill is a micro high-speed vibration ball mill, model MSK-SFM-12M-220V.

[0046] 4) The mixed solution of Co(NO3)2·6H2O and Fe(NO3)3·9H2O after sufficient shaking in step 3) was mixed with ethanol in an equal volume ratio of 1:1 and subjected to ultrasonic treatment for 30 minutes to improve the wettability of the mixed solution to obtain a catalytic solution, such as Figure 1 As shown in a in .

[0047] 5) Use a paper cutter to cut 1*2cm raw carbon paper TGPH060 as a carrier.

[0048] 6) Apply the catalytic solution prepared in step 4) on the raw carbon paper TGPH060 cut to a size of 1*2 cm. The catalytic solution is applied to both sides of the raw carbon paper TGPH060. The amount of catalytic solution applied on each side is 40 μl and the application area is 1*1 cm. Repeated application is performed to ensure that the applied catalytic solution is evenly distributed. Finally, dry under an infrared lamp for 10 minutes.

[0049] 7) The raw carbon paper TGPH060 loaded and dried in step 6) is placed in a muffle furnace, and the temperature of the muffle furnace is raised to 400°C at a rate of 5°C / min. After maintaining for 1 hour, it is naturally cooled to finally obtain a self-supported water electrolysis anode of Co(NO3)2·6H2O and Fe(NO3)3·9H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst.

[0050] The electrochemical performance of the Co(NO3)2·6H2O and Fe(NO3)3·9H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst self-supporting water electrolysis anode prepared by the method of this embodiment is tested as follows: In 25 o C, in 0.5M H2SO4 solution, a three-electrode system was used with a graphite rod as the counter electrode, Hg / Hg2SO4 as the reference electrode, and the Co(NO3)2·6H2O and Fe(NO3)3·9H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst self-supporting water electrolysis anode prepared by the method of this embodiment as the working electrode, and the catalytic performance of the working electrode was tested using a CHI660e electrochemical workstation.

[0051] Figure 5 This is a graph showing the test results of the electrolysis stability of the Co(NO3)2·6H2O and Fe(NO3)3·9H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst self-supported electrolytic water anode prepared in this embodiment in 0.5M H2SO4 solution. From the analysis of the graph, it can be seen that the change in oxygen evolution potential is extremely small, which proves the extremely strong stability of the Co(NO3)2·6H2O and Fe(NO3)3·9H2O bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst self-supported electrolytic water anode. Example 3

[0052] A method for preparing a self-supporting anode for water electrolysis using a bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst comprises the following steps: 1) Prepare 2.0 M Ni(NO3)2·6H2O aqueous solution and 2.0 M Fe(NO3)3·9H2O aqueous solution with deionized water.

[0053] 2) The Ni(NO3)2·6H2O aqueous solution and the Fe(NO3)3·9H2O aqueous solution prepared in step 1) are thoroughly shaken and mixed in an equimolar ratio of Ni and Fe to obtain a mixed solution of Ni(NO3)2·6H2O and Fe(NO3)3·9H2O.

[0054] 3) Select 2 ml of the mixed solution of Ni(NO3)2·6H2O and Fe(NO3)3·9H2O prepared in step 2) and add it to a PE ball mill, then add zirconium oxide microspheres, set the parameters of speed to 5000 rpm and time to 180 s, and oscillate 10 times every half an hour to ensure sufficient mixing and uniform oscillation; wherein, the PE ball mill is a micro high-speed vibration ball mill, model MSK-SFM-12M-220V.

[0055] 4) The mixed solution of Ni(NO3)2·6H2O and Fe(NO3)3·9H2O after sufficient shaking in step 3) was mixed with ethanol in an equal volume ratio of 1:1 and subjected to ultrasonic treatment for 30 minutes to improve the wettability of the mixed solution to obtain a catalytic solution, such as Figure 1 As shown in c.

[0056] 5) Use a paper cutter to cut 1*2cm raw carbon paper TGPH060 as a carrier.

[0057] 6) Apply the catalytic solution prepared in step 4) on the raw carbon paper TGPH060 cut to a size of 1*2 cm. The catalytic solution is applied to both sides of the raw carbon paper TGPH060. The amount of catalytic solution applied on each side is 40 μl and the application area is 1*1 cm. Repeated application is performed to ensure that the applied catalytic solution is evenly distributed. Finally, dry under an infrared lamp for 10 minutes.

[0058] 7) The raw carbon paper TGPH060 loaded and dried in step 6) is placed in a muffle furnace, and the temperature of the muffle furnace is raised to 400°C at a rate of 5°C / min. After maintaining for 1 hour, the temperature is naturally cooled to obtain the bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst self-supporting water electrolysis anode.

[0059] The above description is only a preferred specific implementation manner of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention should be included in the scope of protection of the invention.

Claims

1. A method for preparing a self-supporting electrolytic water anode with a bimetallic site oxygen-coupled electrolytic acidic medium oxygen evolution catalyst, characterized in that: The following steps are involved: 1) Dissolving two nitrates in deionized water to prepare two 2.0 M nitrate aqueous solutions; 2) mixing the two nitrate aqueous solutions prepared in step 1) in an equal molar ratio of the non-precious metal to obtain a mixed solution; 3) Select the mixed solution prepared in step 2) and add it into a PE ball mill, and shake it thoroughly; 4) mixing the mixed solution after sufficient oscillation in step 3) with ethanol and performing ultrasonic treatment to improve the wettability of the mixed solution to obtain a catalytic solution; 5) applying the catalytic solution prepared in step 4) on the carrier, applying the catalytic solution on both the front and back sides of the carrier, and drying under an infrared lamp; 6) placing the carrier loaded and dried in step 5) in a muffle furnace, heating it to 400° C. and annealing it in air, and finally obtaining the bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst self-supporting water electrolysis anode.

2. The method for preparing the self-supporting water electrolysis anode of the bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst according to claim 1, characterized in that: In step 1), the two 2.0 M aqueous nitrate solutions prepared are any two of Co(NO3)2·6H2O, Ni(NO3)2·6H2O, and Fe(NO3)3·9H2O.

3. The method for preparing the self-supporting water electrolysis anode of the bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst according to claim 2, characterized in that: In step 1), the two 2.0 M nitrate aqueous solutions prepared are Co(NO3)2·6H2O and Ni(NO3)2·6H2O.

4. The method for preparing a self-supporting anode for water electrolysis with a bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst according to claim 1, characterized in that: In step 3), select 2 ml of the mixed solution and add it to a PE ball mill, then add zirconium oxide microspheres, set the speed to 5000 rpm and the time to 180 s, and shake it thoroughly 10 times every half an hour.

5. The method for preparing the self-supporting water electrolysis anode of the bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst according to claim 1, characterized in that: In step 4), the mixed solution after sufficient shaking was mixed with ethanol in an equal volume ratio of 1:1, and the ultrasonic treatment time was 30 minutes.

6. The method for preparing a self-supporting anode for water electrolysis with a bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst according to claim 1, characterized in that: In step 5), the carrier is raw carbon paper TGPH060.

7. The method for preparing a self-supporting anode for water electrolysis with a bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst according to claim 6, characterized in that: The cutting size of the raw carbon paper TGPH060 is 1*2 cm, the amount of the catalytic solution applied to the front and back sides is 40 μl, the application area is 1*1 cm, and the drying time under the infrared lamp is 10 min.

8. The method for preparing a self-supporting anode for water electrolysis with a bimetallic site oxygen-coupled electrolysis acidic medium oxygen evolution catalyst according to claim 1, characterized in that: In step 6), after the carrier is placed in the muffle furnace, the temperature of the muffle furnace is raised to 400° C. at a rate of 5° C. / min, maintained for 1 hour, and then cooled naturally.